The command and prohibition and its indication - Kamaruszaman, Muhammad Hazim; Rohadi, Muhammad Arif Izzuddin; Mazlan, Muhammad Hasif; Nasir, Ahwaz Ahmad (2025)
Slide presentation for "The command and prohibition and its indication"